The Effect of Attitude Subjective Norms, Perceptions of Control Behaviour, Professional Commitments and Gender on Wistleblowing Intention - Vierina Clyde; Mazda Tjahjono (Jurnal Riset Akuntansi Terpadu, 2021)
This study aims to determine the effect of professional commitment, attitudes, subjective norms, perceptions of behavioral control, and demographics on the intention to take whistleblowing actions. Respondents in this study were 187 internal auditors representing inspectorates throughout Banten Province. This study uses primary data to obtain information from respondents using purposive sampling method. SPSS 23 was used in this study to analyze the research which consisted of descriptive statistics and hypothesis testing. Results This study shows that attitudes, subjective norms, perceptions of behavioral control and professional commitment have a significant effect on the intention to take whistleblowing actions. Meanwhile, gender has no significant effect on the intention to do whistleblowing.